Preliminary Analysis of an Internal Annuloplasty Ring for the Aortic Valve - Sadeghi Malvajerdi, Neda (Université d'Ottawa / University of Ottawa, 2017)
Among the four valves of the heart, the aortic valve (AV) is frequently affected by disease. When progressive dilatation of the valve produces a leak when the valve should close (regurgitation), repair may be possible. AV repair is a desirable option because, contrary to AV replace-ment using a prosthesis, it does not require life-long anticoagulation treatment, and retains the original tissues that naturally combat structural degradation. All the AV repair procedures developed by cardiac surgeons require a good stabilization of the ventriculo-aortic junction (VAJ) diameter, through annuloplasty or reimplantation, for long-term success. In the present work, a preliminary design for a new type of annuloplasty ring is proposed that surgeons could tailor to the each valve’s shape and suture inside the VAJ. The design consists in wrapping a commonly available surgical biomaterial into a ring of controlled radial flexibility. For sizing and material selection, several models of increasing complexity were created to account for the anisotropic, hyperelastic nature of all the materials involved. First, an analytical model was programmed in MATLAB to assess the radial flexibility of annuloplasty rings formed with different biomaterials and select those that could match the physiological VAJ radial flexibility between systolic and diastolic pressures. The same program was also used to reproduce the experimental radial and longitudinal stretches of the human VAJ from 0 to 140 mmHg pressures. The analytical models were used to calibrate the parameters of independent finite element (FE) models of the VAJ and ring. Finally, the FE approach was extended to simulate the ring after suturing inside the VAJ, to determine the radial flexibility of the assembly under pulsatile pressure. Supple Peri-Guard® bo-vine pericardium patches used in transverse orientation emerged as the best currently available material option for the proposed ring, although a material providing more physiological radial flexibility would be desirable.
Keywords: Aortic valve; Aortic regurgitation; Reimplantation; ventriculo-aortic junction (VAJ); Finite element (FE); Supple Peri-Guard(SPG); Internal annuloplasty Ring; Aortic stenosis; Heart anatomy and physiology; Sinotubular junction (STJ); Mechanical heart valves; Tissue valves; pericardium; CellScale biaxial tester; Guccione model